Bone tumours in man and animals - Owen, L. N. (Butterworth, 1969)
Bone Tumours in Man and Animals covers advances in the understanding of the pathogenesis of bone neoplasia in humans and animals as well as their diagnosis and treatment. In the case of animals, particular emphasis is placed on dogs.